2017
DOI: 10.1016/j.bbmt.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Lenalidomide Therapy for Persistent Chronic Lymphocytic Leukemia after Allogeneic Transplantation

Abstract: In patients with chronic lymphocytic leukemia (CLL), persistence of disease after allogeneic stem cell transplantation (alloSCT) can result in poor outcomes. In an effort to improve these outcomes, patients with persistent CLL who were 90 to 100 days beyond alloSCT with no evidence of graft-versus-host-disease (GVHD) were randomized to receive lenalidomide or standard care (withdrawal of immunosuppression followed by donor lymphocyte infusion). Lenalidomide was initiated at 5 mg every other day and increased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…Patients were treated with an oral dose of 10 or 15‐mg Len daily and given continuously until documented progressive disease (PD) or intolerability. The doses of Len were based on the previous studies, some of which showed a development of severe GVHD during Len among posttransplant patients . Therefore, patients were treated with reduced dose, such as 10 to 15 mg/day, of Len, referring the starting dose of maintenance therapy for relapsed multiple myeloma after allo‐HSCT …”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Patients were treated with an oral dose of 10 or 15‐mg Len daily and given continuously until documented progressive disease (PD) or intolerability. The doses of Len were based on the previous studies, some of which showed a development of severe GVHD during Len among posttransplant patients . Therefore, patients were treated with reduced dose, such as 10 to 15 mg/day, of Len, referring the starting dose of maintenance therapy for relapsed multiple myeloma after allo‐HSCT …”
Section: Methodsmentioning
confidence: 99%
“…The doses of Len were based on the previous studies, some of which showed a development of severe GVHD during Len among posttransplant patients. [31][32][33][34][35] Therefore, patients were treated with reduced dose, such as 10 to 15 mg/day, of Len, referring the starting dose of maintenance therapy for relapsed multiple myeloma after allo-HSCT. 31,33,34 Regarding patients whose creatinine clearance of 30 to 50 mL/ min, the starting dose of Len was reduced to 40% from 10 mg daily (ie, 5 mg every other day as a minimum dose).…”
Section: Treatmentmentioning
confidence: 99%
See 3 more Smart Citations